FORMULATION AND EVALUATION OF MUCOADHESIVE BUCCAL TABLET OF DOMPERIDONE MALEATE - Dixit, Yuwaraj Dilipsingh; Suruse, Pravin Babarao; Shivhare, Umesh Dhaniram (Indonesian Journal of Pharmacy, 2013)
The objective of the present study was to develop and evaluate mucoadhesive dosage form of Domperidone maleate. It is an antiemetic synthetic benzimidazole compound that acts as a dopamine D2 receptor antagonist. Mucoadhesive Domperidone maleate tablet formulation was prepared by direct compression method. The formulation F3 containing (Carbopol 940 + sodium alginate) was found to be best among all the formulation batches because of its consistent release rate for 7 h and extent of drug release was 94.44%. Graphical treatment of the formulation F3 to Higuchi’s equation showed that the drug release was diffusion mediated. In-vitro permeability study for formulation F3 for 7 h had shown 76.69% drug release. FTIR studies showed no evidence on interaction between drug and polymers. Key words: Domperidone maleate, Mucoadhesive tablet, antiemetic